Tomada de decisão baseada em lógica fuzzy e na distribuição espacial da mortalidade por acidentes de trânsito na cidade de João pessoa PB. - Costa, Danielly Cristina de Souza (2011)
From decade of 80 the external causes, especially traffic accidents, have become a big problem that afflicts the Brazil and the World. This work aims to study the traffic accidents in the city of João Pessoa from the spatial distribution and fuzzy logic to the decision making of priority areas and non-priority. The analysis was an initial observation a study of aggregated neighborhood and after separately. The data used in the analysis were of secondary type collected by the Department of Legal Medicine (DML). The analysis carried out were the follows: descriptive statistics, spatial distribution and fuzzy logic. From the results of descriptive statistics found that the males accounted for 562 victims and the female 102 victms of all the years studied in the city of Joao Pessoa. The main means of transport that caused the accidents were the cars followed by motorcycle. The nature of the traffic accidents most frequent were: pedestrian collisions that occurred during the years 2005, 2006, 2008 and 2009, followed by collisions. In the morning and afternoon occurred the highest numbers of accidents due to the large number of vehicles on roads in the city and in the shift dawn the number of fatal accidents decreased. The days of the week were more fatal accidents occurred on Saturday, Sunday and Monday. The main victims of accidents were young people and adults in the age groups of 20 to 24, 25 to 29, 30 to 39 and 40 to 49 years. Spatial analysis the main areas of the city with relatively high risk and significant spatial clusters are: northwest, north, northeast and west of the city of João Pessoa. In these areas included the neighborhood of Cabo Branco, Altiplano Cabo Branco,Centro, Mandacaru, Bessa, Cruz das Armas, Pedro Gondim, Tambauzinho and Tambiá. The decision model was used fuzzy logic which aimed to identify priority areas and non-priority traffic accidents in the city of João Pessoa. Were elaborated four linguistic variables and eleven linguistic terms. The results of logic fuzzy were satisfactory because it reached the objective proposed of identification of priority areas and non-priority in the city of João Pessoa. Enabling the decision making of public policies more effectives in order to decrease the number of deaths from traffic accidents.q